2017
DOI: 10.4103/tjo.tjo_32_17
|View full text |Cite
|
Sign up to set email alerts
|

Irritant contact keratitis caused by the bodily fluids of a brown marmorated stink bug

Abstract: PURPOSE:The brown marmorated stink bug is native to Asia (China, Taiwan, Japan, and the Korean peninsula). Its bodily fluids are toxic and irritating to the human skin and eyes. Human case reports are rare. Only one report of irritant contact dermatitis has been published. We report a case of irritant contact keratitis resulting from the chemical components of the bodily fluids of the bug.MATERIALS AND METHODS:A case report.RESULTS:A 74-year-old male presented to our emergency department with pain and redness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The common term 'stink bug' alludes to the bugs' ability of secreting a foul odor from their scent glands (Tsuyuki et al 1965). This smell is thought to have the dual function of alarming nearby conspecifics and deterring predators (Krall et al 1999;Shen and Hu 2017).…”
Section: Life History Of Pentatomidaementioning
confidence: 99%
“…The common term 'stink bug' alludes to the bugs' ability of secreting a foul odor from their scent glands (Tsuyuki et al 1965). This smell is thought to have the dual function of alarming nearby conspecifics and deterring predators (Krall et al 1999;Shen and Hu 2017).…”
Section: Life History Of Pentatomidaementioning
confidence: 99%
“…H. halys is a polyphagous pest that can feed on at least 88 host plants including fruits, vegetables, crops, nuts, weeds, and wild plants ( Bergmann et al, 2016 ; Botch and Delfosse, 2018 ). This pest often invades human dwellings and commercial buildings and secretes volatile compounds that have a detrimental effect on human skin and eyes ( Anderson et al, 2012 ; Shen and Hu, 2017 ). Two previous studies have reported transcriptome datasets from distinct developmental stages of H. halys , but neither of these studies involved the antennal transcriptome, especially chemosensory genes ( Ioannidis et al, 2014 ; Sparks et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stink bugs (Hemiptera: Pentatomidae) can excrete odorous bodily fluids as a defensive strategy when they are disturbed or crushed (Shen and Hu 2017 ). They are also known as shield bugs for their shield shape.…”
mentioning
confidence: 99%